The European Certificate in Medical Genetics and Genomics (ECMGG) - Turnpenny, Peter D.; Pölsler, Laura; Moog, Ute; Tobias, Edward S.; Peron, Angela; Boonen, Susanne E.; Lynch, Bonnie; Berg, Jonathan (European journal of human genetics, 2025)
The European Certificate in Medical Genetics and Genomics (ECMGG) is the official knowledge-based, end-of-specialist training examination designed and delivered by the Union Européenne des Médecins Spécialistes - Section of Medical Genetics (UEMS-SMG). The examination is a joint venture of the SMG, the European Society of Human Genetics (ESHG), and the European Board of Medical Genetics (EBMG). Sittings have taken place in 2019 and 2021-24, and it is gaining in reputation as a high-quality, high-standard assessment. In 2024 the ECMGG underwent satisfactory appraisal by the UEMS-Council of European Specialist Medical Assessment (CESMA). This paper describes the development of the ECMGG, its structure, outcomes, and its meaning for the standards and harmonisation of the specialty of Medical Genetics throughout Europe.
Veröffentlicht: 02. Juli 2025
Gesehen am 05.11.2025